Efektivitas Konsentrasi Ekstrak Organik Daun Sirih Hutan (Piper aduncum L.) terhadap Mortalitas Ulat Penggerek Tongkol Jagung (Helicoverpa armigera Hubner) di Laboratorium - Zahra, Oktannisa; Rustam, Rusli (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2025)
Corn (Zea mays L.) is the one of main food commodity after rice which has a strategic role in agricultural development and the national economy. One of the main pests that attack corn plants is the corn cob borer caterpillar (Helicoverpa armigera Hubner). Alternative control that can be done to reduce the negative impact of synthetic insecticides is using botanical insecticides. Pest control can be carried out using botanical insecticides forest betel leaf (Piper aduncum L.). This research aims to obtain the concentrations of forest betel leaf organic extract that is effective on the mortality of corn cob borer caterpillar H. armigera. This research was conducted at the Plant Pest Laboratory, Faculty of Agriculture and the Natural Materials and Minerals Laboratory, Faculty of Engineering, Riau University from January to March 2024. This research used a completely randomized design (CRD) with five treatments and four replications resulting in 20 experimental units. The treatments given were various concentrations (0%, 0.25%, 0.50%, 0.75%, and 1%) of organic extracts of forest betel leaf. The results showed that the application of organic extract of forest betel leaf had a significant effect on the mortality of H. armigera. 0.75% concentration of organic extract of forest betel leaf was effective in controlling H. armigera which caused a total mortality of 85%, with an initial time of death at 4.75 hours after application, lethal time 50 at 33 hours after application.